The clinic ebook A novel. - Quinn, Cate (2024)
"A superior, creeping psychological thriller taut with tension and drama." — The Seattle Times "Easily the creepiest setting for a suspense novel since the Overlook Hotel in Stephen King's The Shining." —BookPage From the critically acclaimed author of Black Widows comes a thriller set in a remote rehab clinic on the Pacific Northwest coast, in which the death of a woman inside prompts her sister to enter the clinic as a patient in order to find the truth. Perfect for fans of Stacy Willingham and Tarryn Fisher! Meg works for a casino in LA, catching cheaters and popping a few too many pain pills to cope, following a far different path than her sister Haley, a famous actress. But suddenly reports surface of Haley dying at the remote rehab facility where she had been forced to go to get her addictions under control. There are whispers of suicide, but Meg can't believe it. She decides that the best way to find out what happened to her sister is to check in herself—to investigate what really happened from the inside. Battling her own addictions and figuring out the truth will be much more difficult than she imagined, far away from friends, family—and anyone who could help her.